A framework model to determine groundwater contamination risk based on a L-Matrix of aquifer vulnerability and hazardous activity indices - Pacheco, Fernando António Leal; Lima, Victor Hugo Sarrazin; Pissarra, Teresa Cristina Tarlé [UNESP]; do Valle Junior, Renato Farias; Silva, Maytê Maria Abreu Pires de Melo; de Melo, Marília Carvalho; Valera, Carlos Alberto; Moura, João Paulo; Fernandes, Luís Filipe Sanches (Elsevier, 2022)
The method presented in this study assesses groundwater contamination risk using a L-Matrix system approach. The L-Matrix in this case is a cartesian diagram where the XX-axis represents aquifer vulnerability (0≤V≤1) determined by the well-known DRASTIC model, and the YY-axis represents the potential hazardousness (0≤H≤1) of an activity (infrastructural development, industrial activities, livestock and agriculture) measured by a European Commission approach. The diagram is divided into four regions, the boundaries of which are set to V = 0.5 and H = 0.5. Watersheds are represented in this diagram considering their V and H indices, and assigned a potential contamination risk if groundwater sites located within their limits show contaminant concentrations above legal limits for a given use. Depending on the region the watershed falls in the L-Matrix diagram, different management or contamination prevention actions are highlighted: activity development, activity monitoring, activity planning or activity inspecting. Watersheds located in the inspecting region and simultaneously evidencing contamination risk require immediate action, namely conditioning or even suspension of use. The method is tested in the Paraopeba River basin (Minas Gerais, Brazil), a densely industrialized basin that was recently affected by an iron-ore mine tailings dam break. • The L-Matrix diagram highlights different groundwater susceptibility realities experienced by watersheds with different combinations of aquifer vulnerability and activity hazardousness, namely possibility for potential expansion of new hazardous activities but also the necessity to periodically inspect and eventually condition or suspend others. • The L-Matrix diagram is likely a better approach to implement contamination prevention measures in watersheds, than the integrated contamination risk index used by most methods.
Keywords: A framework model to determine groundwater contamination risk based on a L-Matrix of aquifer vulnerability and hazardous activity indices; Aquifer; Contamination likelihood; Potentially harmful activity